Trends in age-specific coronary heart disease mortality in the European Union over three decades: 1980-2009. - Nichols, M; Townsend, N; Scarborough, P; Rayner, M (2013)
AIMS: Recent decades have seen very large declines in coronary heart disease (CHD) mortality across most of Europe, partly due to declines in risk factors such as smoking. Cardiovascular diseases (predominantly CHD and stroke), remain, however, the main cause of death in most European countries, and many risk factors for CHD, particularly obesity, have been increasing substantially over the same period. It is hypothesized that observed reductions in CHD mortality have occurred largely within older age groups, and that rates in younger groups may be plateauing or increasing as the gains from reduced smoking rates are increasingly cancelled out by increasing rates of obesity and diabetes. The aim of this study was to examine sex-specific trends in CHD mortality between 1980 and 2009 in the European Union (EU) and compare trends between adult age groups. METHODS: Sex-specific data from the WHO global mortality database were analysed using the joinpoint software to examine trends and significant changes in trends in age-standardized mortality rates. Specific age groups analysed were: under 45, 45-54, 55-64, and 65 years and over. The number and location of significant joinpoints for each country by sex and age group was determined (maximum of 3) using a log-linear model, and the annual percentage change within each segment calculated. Average annual percentage change overall (1980-2009) and separately for each decade were calculated with respect to the underlying joinpoint model. RESULTS: Recent CHD rates are now less than half what they were in the early 1980s in many countries, in younger adult age groups as well as in the population overall. Trends in mortality rates vary markedly between EU countries, but less so between age groups and sexes within countries. Fifteen countries showed evidence of a recent plateauing of trends in at least one age group for men, as did 12 countries for women. This did not, however, appear to be any more common in younger age groups compared with older adults. There was little evidence to support the hypothesis that mortality rates have recently begun to plateau in younger age groups in the EU as a whole, although such plateaus and even a small number of increases in CHD mortality in younger subpopulations were observed in a minority of countries. CONCLUSION: There is limited evidence to support the hypothesis that CHD mortality rates in younger age groups in the member states of the EU have been more likely to plateau than in older age groups. There are, however, substantial and persistent inequalities between countries. It remains vitally important for the whole EU to monitor and work towards reducing preventable risk factors for CHD and other chronic conditions to promote wellbeing and equity across the region.